A Political Ontology of the Pandemic: Sovereign Power and the Management of Affects through the Political Ontology of War - Lehtinen, Mattias; Brunila, Tuukka (Frontiers in Political Science, 2021)
The COVID-19 pandemic has made visible both the limits and the justification of sovereign power as nation states utilize high degrees of power over populations in their strategies of countering the virus. In our article we analyze a particularly important facet of the strategy of sovereignty in managing the pandemic, which we term the ontology of war. We analyze the way in which war plays a significant role in the political ontology of our societies, through its aiming to produce a unified political subject and an external enemy. Taking our theoretical que from Butler’s thinking on frames of recognizability we extend her theory through augmenting it with a theory of social imagination and affect theory to argue for how the frame of recognizability produced by the ontology of war fails to guide our understanding of the pandemic as a political problem, a failure that we analyze through looking at the affective register. We argue that the main affect that the nation state tries to manage, in relation to the pandemic, through the ontology of war is anxiety. We show that the nation state tries to alleviate anxiety by framing it through the ontology war, this leads to the appearance of a potentially racist and nationalist affective climate where the “enemy” is no longer felt to be the virus, but members of other nations as well as minorities. We argue that the pandemic reveals both the political ontology of war central to the foundation of our political communities, and how this ontology is used by the nation state to manage feelings of anxiety and insecurity. Ultimately, as we will discuss at the end of this article, leads to failure.